(untitled) (Global Media Journal - German Edition, 2016)
When the first boats sank off the coast of Lampedusa, Italy, the debate about refugees and migration started to become one of the most widely discussed issues in mass media and therefore in communication studies again. The concept of framing becomes relevant when investigating the depiction of certain events and issues in news coverage. However, it still lacks a coherent definition. Most recently, it has been argued that a consideration of further elements is necessary in order to restructure the concept. Thus, the present case-study focuses on a combination of linguistic elements used in recent migration discourse and a potential impact of language on news frames. The results of a combined frame and corpus-based analysis of the German Süddeutsche Zeitung and the English Guardian show that connotation of key words used in news frames about the Lampedusa incident between October 2013 and October 2014 diverge from the orientation of news frames. Although approximately two thirds of the examined articles use protection frames, the majority of the identified key words describing refugees is connoted negatively. The fact that these contrary orientations of news frames and connotation do exist serves as a first indication for linguistic elements as influencing factors in framing research.